Potential of some Rhizobacteria Isolates Antagonists in Various Formulation to Control Sheat Root Disease (Sarocladium oryzae) on Rice Plants - Majid, Abdul; Dewi, Keke Yunadia Kumala (Badan Penerbitan Fakultas Pertanian (BPFP), Fakultas Pertanian, Universitas Bengkkulu, 2022)
The reserach aims to determine the potential of antagonistic rhizobacteria and is appropriate formulations used to control sheat root disease (Sarocladium oryzae). This research was carried out in July to December 2019 in the Plant and Disease Laboratory and the Greean House Faculty of Agriculture Jember University. The experiment was conducted using a completely slot deposit 5000 randomized design (CRD) 2 factors, namely isolates and formulation. Isolates factors have 4 factors levels; control, Bacillus sp. isolate, Pseudomonas fluorescens isolate, and Bacillus sp. + Pseudomonas fluorescens isolate. The formulation factors has 4 factors levels; glucose 10% + potato water 70% + bacterial starter 20%, Fructose 20% + coconut water 60% + bacteria; starter 20%, glucose 10% + CMC 2% + monmorilonite 68% + bacterial starter 20%, fructose 20% + CMC 2% + kaolin 58% + bacterial starter 20%. The result showed that the treatment of Bacillus sp. with formulation glucose 10% + CMC 2% + monmorilonite 68% + bacterial starter 20%, showed the best result, with a control effectiveness of 78.31%. Key word; Formulation, Rhizobacteria antagonist, Sarocladium oryzae